KONTRIBUSI IMPLEMENTASI MANAJEMEN STRATEJIK DALAM PENGEMBANGAN KURIKULUM TERHADAP MUTU PEMBELAJARAN DI MTS NEGERI GOWA - Lia Nuraini; Muh. Wayong; Ridwan Idris (Jurnal Manajemen Pendidikan, 2026)
One of the components that plays an important role in achieving learning objectives is its contribution to the quality of learning. Where the contribution of strategic management implementation is a process that includes planning, implementation, and evaluation of policies to achieve organizational goals effectively. However, in its implementation there are still obstacles such as teachers who still find it difficult to adapt to curriculum changes and the lack of facilities and infrastructure that support learning. This study aims to describe the contribution of strategic management implementation in curriculum development to the quality of learning at MTs Negeri Gowa. This study uses qualitative techniques with observation, interviews, and documentation. The results of the study indicate that the implementation of strategic management in curriculum development to improve the quality of learning can be monitored by improving student learning outcomes at MTs Negeri Gowa. Improving the quality of learning is carried out by implementing strategic management consisting of planning, implementation, and evaluation in developing the curriculum systematically. This strategy can be realized through the application of the Curriculum and continuous academic monitoring and supervision.